2016
DOI: 10.1111/jfpe.12509
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of pesticide residues in lettuce based on chemical molecular structure coupled with wavelet transform and near infrared hyperspectra

Abstract: To facilitate more quickly and effectively detect the types of pesticide residues on the surface of lettuce, a method involving the chemical molecular structure coupled with wavelet transform (CMS‐WT) was proposed to extract the characteristic wavelength. Five different kinds of pesticide residues were sprayed on the surface of lettuce, respectively, dimethoate, acephate, phoxim, dichlorvos, avermectin (the ratio of pesticides and water were 1:1000). In addition, the near infrared hyperspectral image informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…A total of 450 samples of lettuce were stored in different plastic bags with different labels and carried to laboratory for polarization spectroscopy collection, after being picked off. In addition, quantitative chemical related experiments was carried out and the results showed that the detection of concentration in each group of pesticide residues in lettuce corresponding to the configuration of each spraying pesticide residues in lettuce (Sun et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 450 samples of lettuce were stored in different plastic bags with different labels and carried to laboratory for polarization spectroscopy collection, after being picked off. In addition, quantitative chemical related experiments was carried out and the results showed that the detection of concentration in each group of pesticide residues in lettuce corresponding to the configuration of each spraying pesticide residues in lettuce (Sun et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…It can also be used online in processing lines as a method that requires little or no sample preparation. Some research studies are available in the literature regarding the detection of pesticide residues on a variety of foodstuffs by NIRS, including pesticide residue determination in tomato, green pepper, longan fruit, orange, olive, cucumber, lettuce and propolis samples . These studies demonstrate the utility of NIRS to detect pesticide residues.…”
Section: Introductionmentioning
confidence: 92%
“…A review of hyperspectral imaging studies for safety and quality of fruits and vegetables has also been recently carried out (Crichton et al, ; Washburn, Stormo, Skjelvareid, & Heia, ). Moreover, due to the wide spectrum range of hyperspectral image technology (Sun et al, ), it is necessary to find a suitable feature selection algorithm.…”
Section: Introductionmentioning
confidence: 99%